Pengaruh Kesadaran Merek, Citra Merek, Keterlibatan Media Sosial, dan Kualitas Konten Terhadap Kepercayaan dan Kepuasan Pelanggan - i putu - artaya; Arasy Alimudin (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2026)
This study aims to analyze the influence of brand awareness, brand image, social media engagement, and content quality on brand trust and customer satisfaction at the Narotama University Professional Certification Institute through social media. This study focuses on the service product certification segment, where brand awareness, brand image, social media engagement, and content quality are considered important factors in building customer trust and satisfaction. This study uses a quantitative method with a causal approach, which seeks to identify cause-and-effect relationships between variables. The population in this study consisted of all 2,200 participants of the Narotama University Professional Certification Institute. The sample was taken using a saturated sampling technique, thus covering the entire population of 327 respondents. Brand awareness and brand image do not significantly influence customer satisfaction, while social media engagement and content quality have a positive and significant influence on customer satisfaction. Brand trust also significantly influences customer satisfaction and acts as a mediator in the relationship between brand image and content quality with customer satisfaction. The conclusion of this study is that building customer trust through strong brand awareness, brand image, and good content quality is crucial for increasing customer satisfaction. However, customer engagement on social media only has a significant impact on satisfaction, not trust. This research contributes to the company's understanding of the factors that influence the trust and satisfaction of Narotama University LSP participants.